Altered Regional Cerebral Blood Flow and Brain Function Across the Alzheimer's Disease Spectrum: A Potential Biomarker - Zhang, Qianqian; Wang, Qing; He, Cancan; Fan, Dandan; Zhu, Yao; Zang, Feifei; Tan, Chang; Zhang, Shaoke; Shu, Hao; Zhang, Zhijun; Feng, Haixia; Wang, Zan; et al. (Frontiers in Aging Neuroscience, 2021)
Objective: To investigate variation in the characteristics of regional Cerebral Blood Flow (rCBF), brain activity and intrinsic Function Connectivity (FC) across the Alzheimer’s Disease Spectrum (ADS). Methods: The study recruited 20 individuals in each of the following categories; Alzheimer’s Disease (AD), Mild Cognitive Impairment (MCI), Subjective Cognitive Decline (SCD) and healthy normal (HC). All the participants completed the 3.0T resting-state functional magnetic resonance imaging and arterial spin labelling scans in addition to neuropsychological tests. Additionally, the normalized CBF, Regional Homogeneity (ReHo) and Amplitude of Low Frequency Fluctuation (ALFF) of individual subjects were compared in the ADS. Moreover, changes in intrinsic FC were investigated across the ADS using the abnormal rCBF regions as seeds and behavioral correlations. Finally, a support vector classifier model of machine learning was used to distinguish ADS from HC. Results Compared to the HC subjects, AD patients showed the poorest level of rCBF in the Left Precuneus (LPCUN) and Right Middle Frontal Gyrus (RMFG) among all the participants. In addition, there was a significant decrease in ALFF in the bilateral Posterior Cingulate Cortex (PCC) and Reho in the right PCC. Moreover, RMFG- and LPCUN-based FC analysis revealed that the altered FCs were primarily located in the posterior brain regions. Finally, a combination of altered rCBF, ALFF and Reho in PCC/PCUN showed a better ability to differentiate ADS from HC, AD from SCD and MCI but not MCI from SCD. Conclusions The study demonstrated the significance of an altered rCBF and brain activity on the early stage of ADS. These findings therefore present a potential diagnostic neuroimaging-based biomarker in ADS. Additionally, the study provides a better understanding of the pathophysiology of AD.